DOA BAPA KAMI SEBAGAI LANDASAN TINGKAH LAKU ORANG PERCAYA KEPADA YESUS - Efesus Suratman (Phronesis: Jurnal Teologi dan Misi, 2019)
Humans are free creatures, because humans have a will in their lives, in the ability to implement their thoughts, humans can do what they want, with the advantages that humans have that exceed other God's creatures, humans can be called the pinnacle of all creation systems. However, humans must have a foundation or basis in living life. The Lord's Prayer is a prayer that has deep meaning. There are many studies on the prayer of Our Father from previous researchers, therefore this research focuses on the prayer of our father as the basis for the behavior of believers in Jesus. The method used, namely data collection, is qualitative research, where deep emphasis is placed on the prayer of Our Father from the point of view as the basis for the behavior of believers in Jesus by conducting document studies or library research in obtaining the information or data needed in this study. The results of this research can be said that the prayer of Our Father becomes the foundation of human behavior.